Pathogenic adaptations to host-derived antibacterial copper - Chaturvedi, Kaveri S.; Henderson, Jeffrey P. (Frontiers in Cellular and Infection Microbiology, 2014)
Recent findings suggest that both host and pathogen manipulate copper content in infected host niches during infections. In this review, we summarize recent developments that implicate copper resistance as an important determinant of bacterial fitness at the host-pathogen interface. An essential mammalian nutrient, copper cycles between copper (I) (Cu+) in its reduced form and copper (II) (Cu2+) in its oxidized form under physiologic conditions. Cu+ is significantly more bactericidal than Cu2+ due to its ability to freely penetrate bacterial membranes and inactivate intracellular iron-sulfur clusters. Copper ions can also catalyze reactive oxygen species (ROS) generation, which may further contribute to their toxicity. Transporters, chaperones, redox proteins, receptors and transcription factors and even siderophores affect copper accumulation and distribution in both pathogenic microbes and their human hosts. This review will briefly cover evidence for copper as a mammalian antibacterial effector, the possible reasons for this toxicity, and pathogenic resistance mechanisms directed against it.